Effect of Stress Interactions on Effective Elasticity and Fracture Parameters in the Damage Zones - Cao, Chenghao; Fu, Li-Yun; Fu, Bo-Ye; Guo, Qiang (Frontiers in Earth Science, 2021)
Elastic interactions between fractures will greatly affect the effective elasticity, which, in turn, reshape the effective fracture parameters. The disturbance will be more complex in the fault zone due to the complicated fracture distributions. The problem is addressed in this study by the comparison of two solutions: the analytical solution without stress interactions and the numerical method considering the stress interactions. The resultant difference between the two solutions allows the estimation of stress interactions on elasticity quantitatively. Furthermore, based on the orthorhombic assumption for fracture clustering in the damage zone, effect of stress interaction on the equivalent fractures parameter is estimated. We firstly characterize the fracture parameters in the fault damage zone considering more realistic distributions of fractures. Then, a series of numerical simulations are conducted to study the effective parameters of the fractured model. Finally, assuming the orthorhombic system of the fracture clustering, we invert the crack density and validate the accuracy of the inversion through the incidence-angle seismic velocities. Our numerical results suggest that, the size of fractures will determine the dominated type of stress interactions, and thus significantly reshape the effective properties of the models regardless of the fracture spatial distribution. Furthermore, the stress interactions tend to underestimate the fracture density for models containing long fractures, but generate a relatively satisfactory inverted fracture density for short fractures.